2000
DOI: 10.1097/00043426-200011000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Malnutrition at the Time of Diagnosis on the Survival of Children Treated for Cancer in El Salvador and Northern Brazil

Abstract: We found no relationship between nutritional status and survival in these patients. This implies that future protocols for use in developing countries can be designed to provide optimal treatment intensity despite the high incidence of malnutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
1
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 7 publications
0
40
1
6
Order By: Relevance
“…Nevertheless, other studies did not report similar associations 14 15. More importantly, two recent systematic reviews of 46 studies suggest that the evidence pertaining to malnourishment has largely been based on paediatric cancer patients in developed countries 16 17.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, other studies did not report similar associations 14 15. More importantly, two recent systematic reviews of 46 studies suggest that the evidence pertaining to malnourishment has largely been based on paediatric cancer patients in developed countries 16 17.…”
Section: Introductionmentioning
confidence: 99%
“…The intuitive relationship between poor nutritional status and a poor prospect for survival in children with cancer has been confirmed in most studies, but not in all 1, 9. Altered pharmacokinetics, more severe toxicity (neutropenia) and delay of chemotherapy have been reported in children with malnutrition 10.…”
Section: Introductionmentioning
confidence: 99%
“…4 When we compared our rate of malnutrition with other studies involving Brazilian children with malignant neoplasms, we observed that our rate was lower than the others, 15,17 which is a fact that warrants more profound analysis, since both studies used similar methodology to ours to define malnutrition.…”
Section: Discussionmentioning
confidence: 60%